User influences on knowledge structuring on the Internet: literature survey and case study of a global network of water professionals - Butcher, Juliette; Jeffrey, Paul; Stuetz, Richard (Journal of hydroinformatics, 2005)
This paper presents a review of the literature on information retrieval and knowledge structuring on the Internet and how end-user factors influence these processes. The review demonstrated that variations in users' professional and educational backgrounds are likely to have an important influence on Internet-based knowledge acquisition and structuring. A good knowledge of users is therefore necessary for the successful design of an on-line information service, particularly for multidisciplinary domains such as the water sector which cover a wide range of subject disciplines, and scientific, technological and industrial domains. The implications of the variety of individuals involved in the water sector for structuring information/knowledge on the Internet is demonstrated by analysing the International Water Association's membership database as a function of several variables, including title, job function, organisation type, nationality and fields of interest. The database revealed a wide range of cultural and professional backgrounds, as well as diverse interests between different organisations. As well as having a good understanding of their backgrounds and interests, analysis of how the different users' use the Internet, for example, by looking at web server log files, is recommended for the successful design of web based information/knowledge sharing structures for the water sector.